If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = x + -8 Reorder the terms: 10 = -8 + x Solving 10 = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -1x = -8 + x + -1x Combine like terms: x + -1x = 0 10 + -1x = -8 + 0 10 + -1x = -8 Add '-10' to each side of the equation. 10 + -10 + -1x = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = -8 + -10 -1x = -8 + -10 Combine like terms: -8 + -10 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18
| 3+2(2x+3)=-15 | | -3q+10=7q | | 6g-5-7-6g= | | B-32=15 | | 8x^2-2x+30=0 | | 7-3z=4z | | 9x+100y+29=32x(45+23y) | | 5(x+2)+3x=74 | | 6j=3+9j | | 9x^2-29=7 | | -3(x+1)-57=6x-9(x+8) | | 2g+8=g | | -6z=-5z-6 | | 5y+1.8=4y-3,2 | | -2y=6-3y | | 9x+100=8x+211111 | | 2(x+5)-(2x+10)=0 | | z^3-3z^2+z-3i=0 | | .5x+7=23 | | 4k=-6+3k | | .66x+2=5 | | 5(x+2)=(5x+10) | | 9x+100=8x+21 | | 386*0.5t-16t^2=0 | | 5b-5-8b-6= | | -10u+7= | | 5x+3=7-x | | 12-9x=199+2x | | 7x-4-7x-8=5x-5x-15 | | 61+53= | | 9b-6=5b+18 | | (x^3+3x^2-x+5)(-x^2+5)= |